2020
DOI: 10.1073/pnas.2002635118
|View full text |Cite
|
Sign up to set email alerts
|

Control of septum thickness by the curvature of SepF polymers

Abstract: Gram-positive bacteria divide by forming a thick cross wall. How the thickness of this septal wall is controlled is unknown. In this type of bacteria, the key cell division protein FtsZ is anchored to the cell membrane by two proteins, FtsA and/or SepF. We have isolated SepF homologs from different bacterial species and found that they all polymerize into large protein rings with diameters varying from 19 to 44 nm. Interestingly, these values correlated well with the thickness of their septa. To test whether r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…FtsA and SepF have been characterized previously in Spn ( Mura et al, 2016 ; Perez et al, 2019 ). FtsA is essential and always co-localizes with FtsZ in Spn , whereas Δ sepF deletion mutants form elongated, widened cells lacking septal constrictions, suggesting that SepF polymers mediate FtsZ-ring closure during septation, possibly by acting as a curved clamp at the leading edge of the closing septum ( Wenzel et al, 2021 ). Despite these phenotypes, Δ sepF mutants grow, similarly, to WT in BHI broth, and the cell morphology defects of Δ sepF mutants are largely reversed by FtsA overexpression ( Mura et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…FtsA and SepF have been characterized previously in Spn ( Mura et al, 2016 ; Perez et al, 2019 ). FtsA is essential and always co-localizes with FtsZ in Spn , whereas Δ sepF deletion mutants form elongated, widened cells lacking septal constrictions, suggesting that SepF polymers mediate FtsZ-ring closure during septation, possibly by acting as a curved clamp at the leading edge of the closing septum ( Wenzel et al, 2021 ). Despite these phenotypes, Δ sepF mutants grow, similarly, to WT in BHI broth, and the cell morphology defects of Δ sepF mutants are largely reversed by FtsA overexpression ( Mura et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study suggested that septal thickness is controlled by curved molecular clamps formed by SepF polymers. The stacking of SepF polymers could be meaningful in septa on the longitudinal direction …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the depletion of SepF in Haloferax volcanii or Mycobacterium tuberculosis results in the formation of large cells or defective growth. Further studies indicated an additional function of SepF in Bacillus subtilis to shape the cell wall due to its intrinsic property of forming ring structures . In M. tuberculosis , SepF could also function as a link between cell division and peptidoglycan synthesis as a consequence of the interaction with MurG …”
Section: Introductionmentioning
confidence: 99%
“…In order to highlight the shape of the cleavage furrow, the ftsZ filaments are depicted perpendicular to the plane of the page. Recent study of sepF indicates that it forms rings with the membrane-interacting surface on the inner face [ 14 ], so it is depicted as forming a C-shaped assembly cupping the membrane. Uncharacterized protein JCVISYN3A_0239 was predicted to have a single transmembrane segment and several spectrin repeats, and was included in a speculative interaction with ftsZ/ftsA similar to EzrA [ 15 ].…”
Section: Narrative Decisionsmentioning
confidence: 99%